Loss And Gain In The Translation Process Of Bilingual Online News - Ida Ayu Made, Dian Wilasita; Putri Rahardian, Zabrina; Balqis Kusumah, Alifia; Agung Istri Aryani, I Gusti (Darussalam English Journal (DEJ), 2024)
This study examines the translation of bilingual online news headlines about Ed Sheeran's concert tour, focusing on the concepts of "loss" and "gain" in the translation process. Through qualitative content analysis, it explores how translators navigate cultural challenges while ensuring the message is clear and relatable for the target audience. The findings reveal that certain details, such as Ed Sheeran’s name and the term "sekaliber," are often omitted, leading to a loss of emphasis and contextual richness. However, translators often introduce new elements, such as personal references, to enhance emotional engagement and relevance. The research highlights that translation is an adaptive process, where adjustments are made to preserve the core message’s impact and resonate with readers. Ultimately, effective translation requires more than a word-for-word conversion; it necessitates a nuanced understanding of both source and target cultures to maintain the essence of the original message despite inevitable shifts in meaning.